Analysis of Central Asian Regional Identity: Unity in Diversity - Shermatova, Sayyora; Pyo, Nari (Journal of Global Politics, 2019)
Recently, the value of Central Asia has been attracting attention due to the changes in the surroundings atmosphere such as “One Belt One Road” and the economic development of its own regional countries. Five major countries in Central Asia: Kazakhstan (Mainly its Southern part), Uzbekistan, Tajikistan, Kyrgyzstan and Turkmenistan share the region with their cultural, ethnical and linguistic characteristics. For many countries, including Korea, this area is still remembered as satellite states of the former Soviet Union. In fact, the memory of the Soviet Union is one of the important elements of identity for the countries in Central Asia. At the same time, other elements such as religious, ethnical and linguistic characteristics are also the factors that make up the identity of the Central Asia. And the Post-Cold War behaves of Central Asian countries even look as if they intentionally have been denied the collective identity of Soviet Union. Since the period of Soviet disintegration, Central Asian countries have made great efforts to establish their national identity. Unlike East Asia, countries in this region have not been conscious of being nation states even in the Modern age, due to their cultural peculiarity including nomadism. In this region, the Cold War incidentally delayed discussions on national identity issue by bundling the region within the boundary of the Soviet Union. Furthermore, after the end of the Cold War, the need for integrated identity emerged in the process of seeking for regional development opportunity, such as cooperation with other regional powers including ”One Belt One Road”. This environment made Central Asia faces to the dual task of establishing individual national identity in each region and building a collective identity for the whole Central Asian region. This paper emphasizes that Central Asia itself needs to establish a new regional identity in a peaceful way in order to overcome its identity issue and take advantage of new opportunity through cooperation. KCI Citation Count: 0